Geochemistry of travertine deposits in the Eastern Anatolia District: an example of the Karakocan-Yogunagac (Elazig) and Mazgirt-Dedebag (Tunceli) travertines, Turkey - Kalender, Leyla; Okan, Ozlem Oztekin; Inceoz, Murat; Cetindag, Bahattin; Yildirim, Vesile (Tubitak Scientific & Technological Research Council Turkey, 2015)
The Karakocan-Yogunagac (Elazig) and Mazgirt-Dedebag (Tunceli) travertines, which are related to thermal springs, are situated on the right-lateral strike-slip Karakocan Fault Zone (KFZ) and left-lateral strike-slip Pamuklu Fault Zone (PFZ) in eastern Anatolia. The surface area of the travertines varies from m(2) to km(2). Morphologically, the travertines are classified as ridge, banded, and terrace types due to deposition in different ways, in the releasing/restraining bends of the KFZ and PFZ and on the segments of faults. The banded travertines were dated by U-series, and an age of 160,000 +/- 76 years was determined in only one sample from the Mazgirt-Dedebag area. Travertines primarily consist of low magnesian calcite and form the spherical pisoids. Amorphous iron oxide (up to 2.93%), other metal concentrations (As: 753.3 ppm; Co: 14.3 ppm; Cu: 4.9 ppm; Mn: 4094 ppm; Zn: 4.7 ppm), and heavy stabile isotope values (delta O-18(calcite) ((SMOW)) parts per thousand and delta C-13(calcite (PDB))) have increasing trends from the outside to the inside of the banded travertines. The estimated delta O-18(H2O) isotope values in both ancient and modern travertine samples show that the thermal water temperature decreased approximately 17 degrees C from ancient to modern travertine formations. Algal species of Cyanophyta (blue/green algae), Chlorophyceae (green algae), and Bacillariophyta are predominant in both the Mazgirt and Karakocan travertines. Oscillatoria is dominant in the studied thermal waters that are found as superficial mats on the travertines and are often common in sulfide-rich thermal waters.
Keywords: Geochemistry; Mazgirt; Karakocan; Travertine; Turkey